PAKISTAN'S PHARMACEUTICAL CARE ENTERS A NEW ERA WITH THE INTEGRATION OF DIGITAL HEALTH TECHNOLOGIES IN COMMUNITY PHARMACIES (The Research of Medical Science Review, 2025)
The introduction of digital health technologies into community pharmacies signifies a significant change in Pakistan's pharmaceutical care delivery system. With the rising frequency of chronic diseases and a growing emphasis on patient-centered treatment, traditional pharmacy procedures orientated around prescription dispensing are no longer adequate. This research investigates how community pharmacists can become more complete healthcare providers through the use of digital health innovations like tele pharmacy, electronic health records (EHRs), and mobile health (mHealth) technologies. These innovations have the potential to promote patient involvement, optimize clinical workflows, and improve drug management especially in underprivileged areas where access to healthcare is still a barrier. However, there are many obstacles to the use of digital health technology in the nation's pharmaceutical industry, such as inadequate training for pharmacists, regulatory concerns, and a lack of resources. This study evaluates the present level of digital health adoption in Pakistani community pharmacies, looks at the advantages and disadvantages, and makes suggestions to encourage the use of these tools. Community pharmacy can significantly contribute to filling in the gaps in Pakistan's healthcare system and enhancing general wellness by using digital technologies